T‐Cell Phenotypes Predictive of Frailty and Mortality in Elderly Nursing Home Residents. Issue 1 (24th October 2016) - Johnstone, Jennie; Parsons, Robin; Botelho, Fernando; Millar, Jamie; McNeil, Shelly; Fulop, Tamas; McElhaney, Janet E.; Andrew, Melissa K.; Walter, Stephen D.; Devereaux, P.J.; Malek, Mehrnoush; Brinkman, Ryan R.; et al.
Abstract : Objectives: To determine whether immune phenotypes associated with immunosenescence are predictive of frailty and mortality within 1‐year in elderly nursing home residents. Design: Cross sectional study of frailty; prospective cohort study of mortality. Setting: Thirty‐two nursing homes in four Canadian cities between September 2009 and October 2011. Participants: Nursing home residents aged 65 and older (N = 1, 072, median age 86, 72% female). Measurements: After enrollment, peripheral blood mononuclear cells were obtained and analyzed using flow cytometry for CD4 + and CD8 + T‐cell subsets (naïve, memory (central, effector, terminally differentiated, senescent), and regulatory T‐cells) and cytomegalovirus (CMV)‐reactive CD4 + and CD8 + T‐cells. Multilevel linear regression analysis was performed to determine the relationship between immune phenotypes and frailty; frailty was measured at the time of enrollment using the Frailty Index. A Cox proportional hazards model was used to determine the relationship between immune phenotypes and time to death (within 1 year). Results: Mean Frailty Index was 0.44 ± 0.13. Multilevel regression analysis showed that higher percentages of naïve CD4 + T‐cells ( P = .001) and effector memory CD8 + T‐cells ( P = .02) were associated with a lower mean Frailty Index, whereas a higher percentage of CD8 + central memory T‐cells was associated with a higher mean Frailty Index score ( P = .02). One hundred fifty one (14%) members of the cohort died within 1 year. Multivariable analysis showed a significant negative multiplicative interaction between age and percentage of CMV‐reactive CD4 + T‐cells (hazard ratio = 0.87, 95% confidence interval = 0.79–0.96). No other significant factors were identified. Conclusion: Immune phenotypes found to be predictive of frailty and mortality in this study can help further understanding of immunosenescence and may provide a rationale for future intervention studies designed to modulate immunity.